2021
DOI: 10.1029/2021jg006342
|View full text |Cite
|
Sign up to set email alerts
|

Biological Nitrogen Fixation in Sediments of a Cyanobacterial Bloom‐Occurring Bay in One Eutrophic Shallow Lake: Occurrence and Related Environmental Factors

Abstract: The availability of nitrogen affects primary productivity in aquatic environments (McCarthy et al., 2016;Shiozaki et al., 2018). However, excessive nitrogen loading induced by human activities has increased the frequency and duration of harmful cyanobacterial blooms in lake systems (Paerl & Barnard, 2020;Sinha et al., 2017;Wagner et al., 2021). Eutrophication, particularly an increase in the nitrogen load, promotes the proliferation of non-nitrogen-fixing toxic algae (e.g., Microcystis) by replacing the algae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
(89 reference statements)
2
6
0
Order By: Relevance
“…N fixation has also been attracted attention in freshwater lakes. Yao et al (2018) and Tian et al (2021) reported that N fixation occurred obviously in Taihu Lake, and found that the process rates were comparable to urban rivers as well as estuarine and coastal ecosystems. The concentrations of sulfide, sulfate, and NO 3 − in pore water were critical factors influencing the N fixation in lakes (Tian et al, 2021).…”
Section: Key N Cycling Processes In Various Aquatic Environmentsmentioning
confidence: 94%
See 1 more Smart Citation
“…N fixation has also been attracted attention in freshwater lakes. Yao et al (2018) and Tian et al (2021) reported that N fixation occurred obviously in Taihu Lake, and found that the process rates were comparable to urban rivers as well as estuarine and coastal ecosystems. The concentrations of sulfide, sulfate, and NO 3 − in pore water were critical factors influencing the N fixation in lakes (Tian et al, 2021).…”
Section: Key N Cycling Processes In Various Aquatic Environmentsmentioning
confidence: 94%
“…Yao et al (2018) and Tian et al (2021) reported that N fixation occurred obviously in Taihu Lake, and found that the process rates were comparable to urban rivers as well as estuarine and coastal ecosystems. The concentrations of sulfide, sulfate, and NO 3 − in pore water were critical factors influencing the N fixation in lakes (Tian et al, 2021). Notably, in the most eutrophic aquatic environments of China, the N-fixing cyanobacteria generally break out in summer, which can further increase the more bioavailable N and in return exacerbate eutrophication (Yao et al, 2018).…”
Section: Key N Cycling Processes In Various Aquatic Environmentsmentioning
confidence: 94%
“…Biological nitrogen fixation, a microbial process that converts the reduction of dinitrogen gas (N 2 ) to biologically available ammonium, plays a fundamental role in the primary production of aquatic systems (Vitousek and Howarth, 1991;Arp, 2000;Montoya et al, 2004). Diazotrophs in the aquatic environment are widely distributed among Proteobacteria, Euryarchaeota, Cyanobacteria, Bacteroidetes, and Firmicutes based on the diversity of the nifH gene (Kapili et al, 2020;Wang et al, 2020;Tian et al, 2021a). Diazotrophs capable of fixing molecular nitrogen have been found to be present in the water columns and the sediments of lakes (Zhang and Zhang, 2016;Yao et al, 2018;Wang et al, 2020;Tian et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Diazotrophs in the aquatic environment are widely distributed among Proteobacteria, Euryarchaeota, Cyanobacteria, Bacteroidetes, and Firmicutes based on the diversity of the nifH gene (Kapili et al, 2020;Wang et al, 2020;Tian et al, 2021a). Diazotrophs capable of fixing molecular nitrogen have been found to be present in the water columns and the sediments of lakes (Zhang and Zhang, 2016;Yao et al, 2018;Wang et al, 2020;Tian et al, 2021a). It is traditionally believed that N 2 -fixing Cyanobacteria are the main diazotrophs in aquatic systems (Yao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation